Combination of polymeric micelle formulation of TGFβ receptor inhibitors and paclitaxel produces consistent response across different mouse models of Triple‐negative breast cancer - Natasha Vinod; Duhyeong Hwang; Sloane Christian Fussell; Tyler Cannon Owens; Olaoluwa Christopher Tofade; Thad S. Benefield; Sage Copling; Jacob D. Ramsey; Patrick D. Rädler; Hannah M. Atkins; Eric E. Livingston; J. Ashley Ezzell; et al. (Wiley, 2024)
Abstract Triple‐negative breast cancer (TNBC) is notoriously difficult to treat due to the lack of targetable receptors and sometimes poor response to chemotherapy. The transforming growth factor beta (TGFβ) family of proteins and their receptors (TGFRs) are highly expressed in TNBC and implicated in chemotherapy‐induced cancer stemness. Here, we evaluated combination treatments using experimental TGFR inhibitors (TGFβi), SB525334 (SB), and LY2109761 (LY) with paclitaxel (PTX) chemotherapy. These TGFβi target TGFR‐I (SB) or both TGFR‐I and TGFR‐II (LY). Due to the poor water solubility of these drugs, we incorporated each of them in poly(2‐oxazoline) (POx) high‐capacity polymeric micelles (SB‐POx and LY‐POx). We assessed their anticancer effect as single agents and in combination with micellar PTX (PTX‐POx) using multiple immunocompetent TNBC mouse models that mimic human subtypes (4T1, T11‐Apobec and T11‐UV). While either TGFβi or PTX showed a differential effect in each model as single agents, the combinations were consistently effective against all three models. Genetic profiling of the tumors revealed differences in the expression levels of genes associated with TGFβ, epithelial to mesenchymal transition (EMT), TLR‐4, and Bcl2 signaling, alluding to the susceptibility to specific gene signatures to the treatment. Taken together, our study suggests that TGFβi and PTX combination therapy using high‐capacity POx micelle delivery provides a robust antitumor response in multiple TNBC subtype mouse models.